Miguel Benzo Mestre, Sobre el sentido de la vida, Biblioteca de Autores Cristianos, Madrid, 1971, 214 pp - Valderrey, Carmen (1973)
Fil: Valderrey, Carmen. Colegio Mayor Santa María de la Almudena; España